PENGARUH HARGA, BAURAN PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI PASARAYA SRI RATU SEMARANG - Muh. Abdul Rokim (Universitas Diponegoro, 2014)
Sri Ratu Semarang Department Store is a company engaged in the business of retail or department stores retail shaped. Intense retail competition led to a decrease in the number of visitors and the number of customer complaints about service quality in Sri Ratu Semarang Department Store. This study aimed to determine the effect of price (X1), product mix (X2), and quality of service (X3) on purchase decision (Y) in Sri Ratu Semarang Department Store. Type of the research is explanatory research. The population used is the consumers who shop in Sri Ratu Semarang Department Store. The sample in this study were 100 respondents were calculated using the formula of Slovin. The sampling technique using accidental sampling method. Data collection using questionnaires and interviews. Data analysis using linear regression analysis. The research concludes that price, product mix, and quality of service has significant influence on purchase decision. Price, product mix, and quality of service explain the purchase decision variable at 38.6% where price has influence by 30.4%, product mix by 35.4%, and quality of service by 24%. Price, product mix, and quality of service simultaneously have significant effect on purchase decision in the Sri Ratu Semarang Department Store, where the product mix has the highest influence. Sri Ratu Semarang Department Store suggested to give discount promo more frequently, decorate the room more interesting and attractive, and sell more diverse products. Provide specific guidance to the salesperson in order to provide maximum service to the consumer., such as price, product mix, and quality of service.